Workforce and Performance: Mastering Property Sales and Enhancing Marketing Skills During the COVID-19 Pandemic - Feri Hendriyanto; Rudi Purwono; Sri Pantja Madyawati; Fendy Suhariadi (Dinasti International Journal of Education Management And Social Science, 2024)
The property sector contributed 2.77% to Indonesia's Gross Domestic Product in 2019,. However, 2020 proved to be a challenging year globally due to the outbreak of COVID-19, which significantly disrupted various sectors, including the global economy. The extent of financial losses worldwide due to the pandemic has not been precisely quantified. This study explores the impact of the pandemic on the property market, specifically focusing on workforce dynamics, performance metrics, effective property sales strategies during the pandemic, and the enhancement of marketing competencies. Employing a qualitative, descriptive-analytical approach, this research concludes that exceptional property sales during the pandemic require rigorous effort, high performance, and advanced marketing skills. Competence, diligence, and performance are crucial in enhancing the capabilities of individual salespersons and, consequently, boosting organizational profits. This study highlights that the diligent and performance-oriented behaviors of salespersons are pivotal for acquiring and applying knowledge in sales scenarios, which are essential for navigating the complexities of the pandemic-affected market. The resilience shown by property salespersons in terms of time dedication and sustained effort amidst failures underscores their critical role in sustaining business operations during unprecedented times.